Self-Efficacy and Anxiety Level of Third-Trimester Primigravida - Susanti, Susanti; Hassan, Hafizah Che; Aljaberi, Musheer Abdulwahid (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Childbirth anxiety causes changes in a woman's mind during the third trimester. Prolonged worry can make it difficult for pregnant women to focus and cause them to lose confidence. Purpose: This study determines the relationship between self-efficacy and anxiety levels of third-trimester primigravida pregnant women. Methods: This study used cross-sectional data and correlation analysis. The purposive sampling method selected 82 third-trimester pregnant women as the study population. The study sample included 57 third-trimester pregnant women per the inclusion criteria. This study used two questionnaires: the self-confidence scale and the Revised Pregnancy-Related Anxiety Questionnaire (PRAQ-R2). The research results on self-efficacy obtained 63.2% with moderate self-efficacy, while anxiety levels obtained the majority with moderate anxiety at 49.1%. Data analysis using the Spearman Rank correlation test formula obtained a correlation coefficient of 0.645 with a significance of 0.000 (p <0, 05). Conclusion: There is a significant relationship in the self-efficacy of third-trimester primigravida pregnant women with anxiety levels with a strong correlation coefficient.